Comparsion of the Effect of Lactobacillus Acidophilus Suppository and Metronidazol Vaginal Tablet on Bacterial Vaginosis - Asghar Mohamad Poorasl; Manijeh Sayyah Melli; Mohamad Hossein Sorush Barhaghi; Davood Hasanzadeh; Reihaneh Ivanbagha; Hamideh Jafarzadeh (Tehran University of Medical Sciences, 2011)
Background & Aim: Bacterial vaginosis is characterized by an imbalance in vaginal natural discharges due to an overgrowth of anaerobic bacteria as well as a concomitant decrease in the number of lactobacilli and increase in vaginal PH to more than 4.5. Bacterial vaginosis increases the risk of pelvic inflamatory disease, postoperative infection following hysterectomy, cervix abnormal cytology and preterm birth. Microbial resistance and a growing tendency to move toward "natural therapies" have led to increase interests in non-antibiotic treatments for bacterial vaginosis. This study aimed to compare the effects of Lactobacillus acidophilus suppository and Metronidazol vaginal tablet on treatment of bacterial vaginosis. Methods & Materials: In a double-blind, paralled randomized clinical trial, 40 out of 300 participants were included in the study from an out-patient private gynaecology clinic in Tabriz, Iran. The participants were randomly allocated to two treatment groups of Lactobacilli suppository and Metronidazol vaginal tablet. Results: The cure rate for the Metronidazol group and the Lactobacilli supository group were 100 and 75 per cents, respectively. Conclusion: According to the results of this study, Metronidazol was more effective in treatment of bacterial vaginosis than the Lactobacilli suppository. A combination of these medications are suggested for resistant to treatment cases.